SCANNING TRANSMISSION ELECTRON MICROSCOPY FOR QUANTITATIVE MAPPING OF MACROELEMENT CONTENTS OF CARDIAC TISSUE - A. A. Komisov; O. A. Osipova; R. N. Shepel; O. M. Drapkina; P. G. Osipov; K. G. Plaksina; N. V. Malay (Российский кардиологический журнал)
Aim. Development of semiquantitative and quantitative nondestructing method to analyze the spread of chemical elements in myocardium mass up to 100 mg (autopsy).Material and methods. The development was performed on biological specimens of cardiac autopsy of 18 healthy persons without cardiovascular pathology died in traffic accidents. Biological specimens were divided into 3 parts, of those 2 parts by1 gand one —0,1 g, respectively. Parts of1 gmass were used for reference range grounding and fine tune of the detector, and the0,1 gpart was the studied specimen. Preparation of specimens was done by standard methodology. The results of macroelements concentration measurement were taken as reference range. Mapping of element contents was done with nanotechnologies: scanning (SEM FEIQuanta 200) and scanning-transmission (STEM; FEI NovaNanoSEM) electronic microscopy.Results. As a result of the study, first time the method for quality improvement was defined for the mapping of macroelementary contents of biological specimens, i. e. tissues of human organs, with x-ray fluorescent analysis. The data makes it to study the spread of microand macroelements in myocardium that provides benefits in comparatory analysis, assessing dislocations, foci of pathological concentrations of elements in tissues of cardiovascular patients.Conclusion. The method of macroelement contents mapping of biological specimens with x-ray fluorescence makes it to improve the precision of mapping of macroelementary contents in biological specimens 100 times up to 10-30 ppm, which is itself a quantitative mapping, and has benefits for practical implication in clinical medicine. The data makes it to study the spread of microand macroelements in myocardium, which opens the opportunity to do comparison of the spread, foci and regions of pathological concentration of chemical elements in the tissue of cardiovascular patients.